Contribución al conocimiento de los laboulbeniales (Ascomycotina) ibéricos, IV. Género Laboulbenia: adiciones y correcciones - Santamaria i del Campo, Sergi (Revista Catalana de Micologia, 2007)
Contribution to the knowledge or Iberian Laboulbeniales (Ascomycotina), IV. GenusLaboulbenia: additions and corrections. Four species of Laboulbenia are here reported as new for theIberian fungus flora: Laboulbenia benjaminii Balazuc, Laboulbenia calathi T. Majewski, LaboulbeniaEtrusca Speg. and Laboulbenia luxurians Peyr. These species are illustrated, described and discussed. Also,Laboulbenia nebriae subsp. maghrebiana Balazuc is included in the list of taxa of the genus as a correctionof a previous record of Laboulbenia nebriae Peyr. s. str.